2003
DOI: 10.1002/chin.200319153
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Potent, Orally Bioavailable Dihydroquinazolinone Inhibitors of p38 MAP Kinase.

Abstract: Fused pyrimidine derivativesFused pyrimidine derivatives R 0515 Design and Synthesis of Potent, Orally Bioavailable Dihydroquinazolinone Inhibitors of p38 MAP Kinase. -A variety of new dihydroquinazoline inhibitors of p38 MAP kinase [cf. (VII) and (X)] are synthesized. Optimization of the C-5 aryl and C-7 piperidinyl substituents results in the identification of compound (X), which gives excellent suppression of TNF-α production and good oral exposure in rats. -(STELMACH*, J. E.; et al.; Bioorg. Med. Chem. Let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Recently, Stelmach et al . have reported potent, orally bioavailable (in a rat model) dihydroquinazolinone hybrid p38α inhibitors based on a pyridinyl imidazole p38α inhibitor developed by Merck and on VX‐745 159 …”
Section: Ongoing Studies and Clinical Perspectivesmentioning
confidence: 99%
“…Recently, Stelmach et al . have reported potent, orally bioavailable (in a rat model) dihydroquinazolinone hybrid p38α inhibitors based on a pyridinyl imidazole p38α inhibitor developed by Merck and on VX‐745 159 …”
Section: Ongoing Studies and Clinical Perspectivesmentioning
confidence: 99%
“…The subsequent responses that TNF ␣ and IL-1 ␤ transmit through their respective receptors lead to induction of additional proinflammatory proteins involved in the pathogenesis of RA that are also mediated through p38 ␣ , including induction of cyclooxygenase 2 (COX-2), matrix metalloproteases (MMPs) 1, 3 and 9, receptor activator of nuclear factor NF-B ligand (RANKL), inducible nitric oxide synthase (iNOS), and integrin expression [20,[22][23][24][25][26][27][28][29][30] . Selective inhibitors of p38 ␣ block the production and activity of these proteins and have demonstrated marked efficacy in animal models of acute inflammation, arthritis and chronic obstructive pulmonary disease [2,25,[31][32][33][34][35][36] . The ability of p38 ␣ inhibitors to reduce the levels of multiple inflammatory cytokines and mediator proteins suggests that these compounds have the potential for enhanced and/or broader efficacy compared with agents restricted to single-cytokine modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Early p38 ␣ inhibitor patents focused on imidazolebased compounds [39,40] and were followed by patents claiming structures based on pyrroles, thiazoles, and oxazoles [35,41], and others with unrelated structures such as the pyrazole ureas [34,36,42,43] . We report here on the preclinical biological evaluation and phase 1 clinical evaluation of SD0006, a diarylpyrazole (DAP).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the piperizine at C7 increased kinase activity and HWB potency. Stelmach et al has reported the related dihydroquinazolines (35, p38α IC 50 0.2 nM, LPS-TNFα HWB IC 50 10.1 nM) in which the lipophilic aryl group is connected at C5 [48]. Optimal C5 aryl substitution includes methyl, mono or dihalogen, and introduction of the piperidine at C7 imparted better PK properties.…”
Section: Fused 66 and Related P38 Map Kinase Inhibitorsmentioning
confidence: 99%